Hepatocellular carcinoma treatment: hurdles, advances and prospects. (28th September 2018) - Kumari, Ratna; Sahu, Manoj Kumar; Tripathy, Anindita; Uthansingh, Kanishka; Behera, Manas
Hepatocellular carcinoma (HCC) is one of the major causes of cancer-related mortality and is particularly refractory to the available chemotherapeutic drugs. Among various etiologies of HCC, viral etiology is the most common, and, along with alcoholic liver disease and nonalcoholic steatohepatitis, accounts for almost 90% of all HCC cases. HCC is a heterogeneous tumor associated with multiple signaling pathway alterations and its complex patho-physiology has made the treatment decision challenging. The potential curative treatment options are effective only in small group of patients, while palliative treatments are associated with improved survival and quality of life for intermediate/advanced stage HCC patients. This review article focuses on the currently available treatment strategies and hurdles encountered for HCC therapy. The curative treatment options discussed are surgical resection, liver transplantation, and local ablative therapies which are effective for early stage HCC patients. The palliative treatment options discussed are embolizing therapies, systemic therapies, and molecular targeted therapies. Besides, the review also focuses on hurdles to be conquered for successful treatment of HCC and specifies the future prospects for HCC treatment. It also discusses the multi-modal approach for HCC management which maximizes the chances of better clinical outcome after treatment and identifies that selection of a particular treatment regimen based on patients' disease stage, patients' ages, and other underlying factors will certainly lead to a better prognosis.